Current concepts on drug abuse and dependence - Daniela Luiza Baconi; Anne-Marie Ciobanu; Ana Maria Vlăsceanu; Oana Denisa Cobani; Carolina Negrei; Cristian Bălălău (Journal of Mind and Medical Sciences)
Drug addiction is a complex disease characterized by compulsive and uncontrollable desire to seek and consume the drug. In time, drug-related terminology has undergone many changes, arising from the deepening of the mechanisms of action, but also about the need for a greater precision in the definition. Drug dependence can be assigned not only to pharmacological effects of the drugs of abuse, but also to their interaction with each particular neurological and psychological constitution. The research on the neurobiological mechanisms of addiction processes allows both a better understanding of current pharmacotherapy and the development of new treatment strategies in drug abuse and dependence. In this review we intend to present the current concepts related to drug abuse and dependence.